Audio visual musical rhythm movement on the ability to brush teeth of intellectually impaired children - Suriakusumah, Sagara; Samjaji, Samjaji; Widyagdo, Agung (Journal Center of Excellent : Health Assistive Technology, 2024)
Background: Maintaining dental and oral health in children with mental retardation is usually still relatively lacking, one of which is in patients with mentally retarded children. Children with mental retardation need to be given more effort to maintain the dental health of mentally retarded children so that they remain healthy. Objective: This study aims to determine the effect of counseling using audio-visual movements to musical rhythms on the ability to brush the teeth of mentally retarded children in SLBN cineam, Tasikmalaya district. Method: Quasi-experiment design with one group pre-test and post-test design. Sampling was taken using a saturated sampling method where the entire population was used as a sample of 30 people. The measuring tool uses an observation sheet. Data analysis using the Wilcoxon test. Results: after being given counseling using audio-visual movements to the rhythm of music, the average ability to brush the teeth of mentally retarded children increased from 3.60 (Fair) to 2.85 (Good). Wilcoxon test results obtained p value = 0.000 (<0.05) . Conclusion: there is an influence of counseling using audio-visual movements to the rhythm of music on the ability to brush the teeth of mentally retarded children at SLBN Cineam, Tasikmalaya Regency.